Reinforcement mechanisms of rock bolt : a laboratory investigation - Mohd. Amin, Mohd. For; Khoo, Kai Siang; Chai, Hui Chon (Faculty of Civil Engineering, UTM, 2004)
The use of rock bolts as rock reinforcement is becoming more popular in Malaysia. However, its effectiveness depends on a number of factors particularly with regards to the technique of installing the bolt. Its reinforcement mechanism also restricts its application for certain modes of instability and types of rock. This paper highlights a laboratory investigation on the reinforcement mechanisms of rock bolts, specifically on bolt inclination, anchorage type and level of pre-tension. The investigation was conducted using a physical model of a rock bolt intersecting a joint plane. Results obtained show that a better reinforcement can be obtained if bolt is inclined at an angle to the joint plane so that it elongates upon joint displacement. Full-bonded bolt is more superior in terms of mobilising the anchorage capacity and consequently, this allows for immediate utilisation of the reinforcing element. Pre-tensioning of bolt induces clamping effect on joint surface consequently, helps to reduce joint dilatation and increases the inherent shear strength of the joint.